Messengers of Eros : representations of sex in Australian writing - Pons, Xavier (Cambridge Scholars Pub., 2009)
This title offers close readings of many Australian literary texts. It revisits classics such as 'Coonardoo', 'Capricornia' or 'Such Is Life' as well as major modern writers such as Patrick White, Peter Carey, David Malouf or Richard Flanagan, and engages with contemporary works whose status is still a matter for debate.